Cutting parameters influence investigations on cutting consumed power, surface roughness and tool wear during turning of superalloy VAT 32 with PVD coated carbide tools using Taguchi method - Kondo, Marcel Y. [UNESP]; Pinheiro, Cleverson [UNESP]; De Paula, Marcelo A [UNESP]; De Souza, Taise A [UNESP]; Souza, José V. C. [UNESP]; Ribeiro, Marcos V. [UNESP]; Alves, Manoel C. S. [UNESP] (IOP Publishing, 2019)
The nickel superalloy VAT 32 was developed as substitute of UNS N07751 alloy in manufacturing of automotive internal combustion valves of high performance. The formation of niobium carbides gives to VAT 32 superalloy a high wear resistance, desirable for application in automotive valves. This creates, however, a higher difficulty in machining this material. This paper studied the turning of VAT 32 with Ti-Al-Si-N coated carbide tool by the physical vapor deposition (PVD) process. The analyses of tool wear, surface quality and cutting power were made. The analyses were made using a Taguchi's method of design of experiments, through L8 orthogonal array. The factors evaluated were cutting speed, feed rate, depth of cut and lubrication condition, dry machining and using abundant lubrication. The influence of the cutting parameters in the analyzed responses were found by analysis of variance (ANOVA) and the optimized set for minimum variability of the process was found by S/N ratio values analyses.
Keywords: cutting potency; machining; nickel-iron based super alloy; optimization